2011
DOI: 10.1523/jneurosci.6665-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Visual Attention Modulates Brain Activation to Angry Voices

Abstract: In accordance with influential models proposing prioritized processing of threat, previous studies have shown automatic brain responses to angry prosody in the amygdala and the auditory cortex under auditory distraction conditions. However, it is unknown whether the automatic processing of angry prosody is also observed during cross-modal distraction. The current fMRI study investigated brain responses to angry versus neutral prosodic stimuli during visual distraction. During scanning, participants were expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 52 publications
(72 reference statements)
5
43
1
Order By: Relevance
“…Thus, our results may be helpful for the debate concerning the automaticity of amygdala activation in the processing of subtle threat (Lipka et al, 2011;Mothes-Lasch et al, 2011;Pessoa and Adolphs, 2010;Pessoa et al, 2006;Straube et al, 2010). At least in healthy subjects, there seems to be no automatic processing of a wide range of threat stimuli given effective prevention of conscious perception.…”
Section: Discussionmentioning
confidence: 74%
“…Thus, our results may be helpful for the debate concerning the automaticity of amygdala activation in the processing of subtle threat (Lipka et al, 2011;Mothes-Lasch et al, 2011;Pessoa and Adolphs, 2010;Pessoa et al, 2006;Straube et al, 2010). At least in healthy subjects, there seems to be no automatic processing of a wide range of threat stimuli given effective prevention of conscious perception.…”
Section: Discussionmentioning
confidence: 74%
“…Besides this activity in the primary and secondary AC for negative expressions, negative and positive expressions revealed activity in the left and right pSTC and mSTC that has previously been shown to be consistently responsive to different types of vocal expression (Fecteau et al, 2007;Frühholz et al, 2012;Grandjean et al, 2005;Johnstone et al, 2006;Kotz et al, 2003;Leitman et al, 2010b;Meyer et al, 2005;Mothes-Lasch et al, 2011;Phillips et al, 1998;Sander et al, 2005;Szameitat et al, 2010;Warren et al, 2006a). Although these regions located in the lateral STC might be a type of higher-level perceptual and feature-integrative representation of vocal expressions, there is evidence that these areas also involve feature sensitivity for vocal expression.…”
Section: Valence Influences Lower-level and Higher-level Auditory Cormentioning
confidence: 79%
“…The emotional cue of a voice can be presented inside the focus of attention (explicit processing of emotion) when participants are asked to explicitly discriminate, classify, or evaluate the emotional tone of a voice (Alba-Ferrara et al, 2011;Beaucousin et al, 2007;Ethofer et al, 2006aEthofer et al, , 2009aFrühholz et al, 2012;Grandjean et al, 2005;Johnstone et al, 2006;Kotz et al, 2003;Leitman et al, 2010b;Mitchell, 2006;Sander et al, 2005;Szameitat et al, 2010;Wildgruber et al, 2005;Wittfoth et al, 2010). This emotional cue can also be presented outside the focus of attention (implicit processing of emotion) when participants are, for example, asked to discriminate the gender of one voice from another (Alba-Ferrara et al, 2011;Bach et al, 2008;Ethofer et al, 2012;Fecteau et al, 2007;Frühholz et al, 2012;Morris et al, 1999;Mothes-Lasch et al, 2011) or to make a linguistic decision about a nonemotional linguistic feature (Buchanan et al, 2000;Ethofer et al, 2006a;Mitchell et al, 2003), or when emotional voices are presented outside the spatial focus of attention Sander et al, 2005). For the latter, Grandjean and colleagues (2005), for example, have shown that a region in the right pSTC is sensitive to vocal expressions independent of attentional focus, whereas an adjacent region in the right mSTC is responsive to vocal expression only when the emotional cue is inside the focus of attention.…”
Section: Introductionmentioning
confidence: 99%
“…We expected, first, that vocalizations, as socially salient stimuli, would generally produce weaker cortical processing in interconnected regions due to unilateral amygdala damage (experiment 1) (39). Second, in keeping with predominant left amygdala activity in healthy individuals during the processing of vocal emotions, we expected more severe impairment in cortical processing of emotional cues in patients with left amygdala lesions compared with right amygdala lesions (experiment 2) (29,40).…”
Section: Significancementioning
confidence: 94%